2015
DOI: 10.1161/hypertensionaha.114.03999
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Central Nervous System MC3/4R Blockade Attenuates Hypertension Induced by Nitric Oxide Synthase Inhibition but Not by Angiotensin II Infusion

Abstract: We examined whether central melanocortin 3 and 4 receptor (MC3/4R) blockade attenuates the BP responses to chronic L-NAME or angiotensin II (Ang-II) infusion in Sprague Dawley rats implanted with telemetry transmitters, venous catheters and intracerebroventricular (ICV) cannula into the lateral ventricle. After 5 days of control measurements, L-NAME (10 μg/kg/day, i.v. – groups 1 and 2) or Ang II (10 ng/kg/min, i.v. – groups 3 and 4) were infused for 24 days and starting on day 7 of L-NAME or Ang II infusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…MC4R antagonism also reduced BP in obese Zucker rats with defective LepR signaling 127 and attenuated BP effects of other peptides besides leptin, including nesfatin-1 and neuronostatin 128,129 . Also, MC4R blockade attenuated hypertension associated with inhibition of NO synthesis but did not lower BP in AngII hypertension which is associated with decreased RSNA 130 . Studies in humans also show that increased MSNA during hypoxic stress is attenuated in MC4R deficient subjects 131 .…”
Section: Autonomic Nervous System and Renal Nerves In Obesitymentioning
confidence: 85%
“…MC4R antagonism also reduced BP in obese Zucker rats with defective LepR signaling 127 and attenuated BP effects of other peptides besides leptin, including nesfatin-1 and neuronostatin 128,129 . Also, MC4R blockade attenuated hypertension associated with inhibition of NO synthesis but did not lower BP in AngII hypertension which is associated with decreased RSNA 130 . Studies in humans also show that increased MSNA during hypoxic stress is attenuated in MC4R deficient subjects 131 .…”
Section: Autonomic Nervous System and Renal Nerves In Obesitymentioning
confidence: 85%
“…Also our previous studies support an important participation of brain MC3/4R in regulating BP in other nonobese models of hypertension. For instance, chronic infusion of MC3/4R antagonist into the lateral ventricles caused marked BP reductions after blockade of nitric oxide synthesis in L-NAME-treated rats, suggesting that endogenous brain MC3/4R activation may play an important role in regulating BP in this model of hypertension [7]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found that chronic infusion of MC3/4R antagonist into the lateral ventricles of lean spontaneous hypertensive rats (SHRs), a model of hypertension associated with high sympathetic tone, markedly reduced their BP to the same degree as accomplished by adrenergic receptor blockade [6]. In addition, chronic MC3/4R antagonism markedly reduced the hypertension induced by chronic nitric oxide synthase inhibition using N G -nitro-L-argenine methyl ester (L-NAME) in lean Sprague–Dawley rats [7]. Therefore, the CNS melanocortin system appears to play a more fundamental role in regulating SNS activity and BP than previously appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…In lean normotensive animals, chronic MC4R antagonism caused sustained bradycardia and reduced BP in spite of hyperphagia and rapid weight gain which normally would evoke tachycardia and elevated BP [56]. Blockade of endogenous MC4R activity also reduced BP in several non-obese experimental models of hypertension, especially those associated with increased SNS activity [42, 57] (Figure 2). For instance, the BP-lowering effects of MC4R antagonism are especially pronounced in spontaneously hypertensive rats (SHR), a genetic model of hypertension that has increased SNS activity [42].…”
Section: Central Actions Of Pomc-mc4r On Blood Pressure Regulationmentioning
confidence: 99%
“…However, MC4R blockade failed to lower BP in angiotensin-II-induced hypertension, an experimental model with baroreflex mediated reductions in SNS activity [57]. These findings highlight the key role of the brain melanocortin system in maintenance of SNS activity and BP in normotensive subjects as well as in non-obese forms of hypertension that have increased sympathetic activity [41, 42, 57, 58]. …”
Section: Central Actions Of Pomc-mc4r On Blood Pressure Regulationmentioning
confidence: 99%